SWOT analysis of the transfer from structural positions to functional positions in the Regional Development Planning Agency (BAPPEDA) of Payakumbuh City using the Grounded Theory method - Daswirman, Daswirman; Syafer, Erdimen; Arda, Edvidel; Heikal, Jerry (CV. ITTC INDONESIA, 2023)
The policy of bureaucracy simplification through the transfer of structural positions (level IV) to specific functional positions designated by the Central Government, which is applied comprehensively to both the Central and Regional Governments, has significant impacts on Civil Servants (PNS) who undergo such position transfers. The Regional Development Agency (Bappeda) of Kota Payakumbuh is one of the Local Government Institutions that has implemented the transfer of positions from structural to functional. This study uses SWOT analysis with the grounded theory method to understand the impacts of this transfer on the career, position, income, quality, and competence of individuals, as well as the work motivation of Civil Servants in Bappeda Kota Payakumbuh after the implementation of this policy. The research findings show that the positive impact of transferring positions from structural to functional includes the opportunity for faster career advancement, which is supported by several factors such as professional recognition, a strong organizational structure, clear job evaluations, and a well-defined job map